Energy-sharing method of smart buildings with distributed photovoltaic systems in area. (August 2022) - Hu, Jie; Li, Peiqiang
Abstract: In the context of smart grid, the joint operation of smart buildings with distributed photovoltaic systems can promote the on-site consumption of photovoltaic power generation and improve its electricity economy. Therefore, this article builds an energy trading framework centered on smart building cluster operators (SBCO), and proposes an energy sharing method for smart buildings with different load types in the region. Considering the difference of time-of-use electricity prices set by the power grid for smart buildings with different load types and the comfort requirements of building users, this method establishes a benefit optimization model based on the master–slave game SBCO and smart buildings for power purchase transactions. Practical examples show that the method in this paper can improve the economic benefits of SBCO and smart buildings, and help to promote the on-site consumption of distributed photovoltaics and optimize the net load characteristics of smart building clusters.